Ethanol Extracts from Selected Tanzanian Medicinal Plants Selectively Inhibit Plasmodium falciparum Growth In Vitro - Christopher, Robert; Msonga, Amina; Hoppe, Heinrich C.; Fabrice F. Boyom (Tanzania Journal of Science, 2023)
This study aimed to assess the in vitro antiplasmodial and cytotoxic activities of ethanol extracts from the root barks, leaves and stem barks of seven medicinal plant species growing in Tanzania. The antiplasmodial activities of extracts against chloroquine-sensitive (3D7) and multidrug-resistant (Dd2) strains of Plasmodium falciparum were determined using a SYBR green I-based fluorescence assay, while the cytotoxicity of active extracts was determined against the human HepG2 cell line using a resazurin-based assay. Out of twenty-one extracts screened, two of them, namely, DFRE from Dracaena fragrans root bark (IC50Pf3D7 = 2.4 mg/mL) and EHSE from Erythrina haerdii stem bark (IC50Pf3D7 = 8.6 mg/mL and IC50PfDd2 = 7.6 mg/mL), exhibited good potencies against P. falciparum parasites. The two extracts emerged as the most promising and selective inhibitors (inhibited the growth of P. falciparum strains and were not toxic to the human HepG2 cell line) of chloroquine-sensitive (3D7) and multidrug-resistant (Dd2) strains of P. falciparum. Eight other extracts showed moderate potencies with IC50 values ranging from 11–25 mg/mL against both plasmodial strains, while the remaining 11 extracts were mildly active with IC50 values ranging from 25.1 to 96.7 mg/mL. The results of the cytotoxicity test indicated that the median cytotoxic concentrations (CC50) of the tested extracts were all ≥ 224.8 mg/mL, leading to selectivity indices (SI) > 10-fold for most of the extracts. The findings described in this article support the traditional use of the investigated medicinal plants to treat malaria. Keywords: Antiplasmodial; Cytotoxicity; Ethanol extracts; Plasmodium falciparum